Entrepreneurship as the nexus of individual and opportunity: A structuration view - Sarason, Yolanda; Dean, Tom; Dillard, Jesse F. (Journal of Business Venturing, 2006)
We propose structuration theory as a useful lens through which to view the entrepreneurial process. Extending Shane and Venkataraman's work (Shane, S., Venkataraman, S., 2000. The promise of entrepreneurship as a field of research. Academy of Management Review 25, 217–226), entrepreneurship is presented as the nexus of opportunity and agency, whereby opportunities are not singular phenomena, but are idiosyncratic to the individual. Entrepreneurial ventures are the medium and outcome of the entrepreneurs' actions. The traditional view of entrepreneurship is that entrepreneurs fill market gaps. A structuration view proposes that the entrepreneur and social systems co-evolve. The presentation of structuration theory offers a robust, and hereto underrepresented, perspective of the entrepreneurial process.